The Unemployment of Today and Tomorrow in Romania - Garlan, Mictat (European Journal of Social Science Education and Research, 2014)
For any political regime the employment and unemployment of active population represents the most pressing social and economic obligation. in Romania, any comparative study before and after 1990, on 2 x 2 decades of different economic policies, can observe the damaging effects which they had forced privatization of state enterprises on the labor market, with over 1,000,000 declared unemployed in 1999, compared to zero unemployed in 1989. After this disaster, and after a short economic rehabilitation, it followed another crisis, with a further increase in unemployment of ANOFM, from 445,000 persons in 2009 to 626,960 persons in 2010 to 740,000 in 2011 of 674,000 in November 2012 , 512 333 persons in December 2013 to 724,000 persons in March 2014. These data indicate that in Romania the crisis is not over yet. in parallel to these developments there have been published the analyzes of the National Commission for Prognosis, but with some significant deviations in two directions. On the one hand, the calculations are made on the formula BIM records, and on the other hand, they are in the direction of a lower estimates. So, in the estimates of performed forecasts for the years 2014 -2017, with trend analysis and analysis of previous years, the total number of unemployed in 2011 was to be of 730 200 persons. in 2012 the total number of unemployed was to be of 701,200 persons, in 2013 of 726,000 persons, of 705,000 persons in 2014, of 690,000 in 2015 and of 685,000 in 2016. Without contesting the effort to accuracy of this Commission and the fact that any forecast includes a dose of risk too, there are obviously immeasurable variables that were not taken into account. We refer to the quality of business environment, revenues polarization, with decreasing trends in wages, to labor migration especially medium and high qualified. We refer to the existing difficulties in the allocation of development credits, to the corruption of officials from the local councils the excess of electoral concerns of governments, with the necessity of different approaches for each of them. With this supplement of fren factors we can say that on prospective 2 years, the registered unemployment from National Institute of Statistics, will not fall below 740.000 persons. To these things, it must be added the volume of more than twice unregistered persons, which means a total of approx. two million persons, this being the actual estimation of the non-employed population, to which has reached in Romania today.